Computação e o ensino superior artístico português: currículos e práticas nos cursos de graduação públicos - Morais, Eduardo (2024)
Undergraduate arts and design programs have been incorporating computing education into their curricula. Through a documentation analysis of the first cycle (i.e., bachelor’s) curricula offered by the Portuguese public education subsystem in the 2018-19 academic year, we identified 40 programs from diverse artistic and design areas, attended by around 5,600 students, which contained at least one course covering computer programming. In a subsequent qualitative analysis of the syllabi of those 128 courses we had identified as relevant, we characterized the objectives, the contents, and the teaching and assessment methods for computing in higher arts education. In the face of the skepticism the literature expresses regarding the validity and robustness of brief approaches to computing, we found most undergraduate programs dedicate few courses or credits (i.e., ECTS) to the topic. We also found programs that introduce the topic late in the curriculum, at a stage when it is likely to meet less dedication from the students. At course level, we note the prevalence of the objective of granting autonomous learning skills to students, which often translates into contents too broad to approach in a non-superficial way. Moreover, we alert to the use of project-based assessment methods in ways that do not assure learning of the contents. With this article we hope to provide an overview of the current situation and contribute to a reflection and a debate about the relevance and the way computing is covered within arts and design education.